The role of diplomatic missions in fostering international trade: A literature review to be considered in the Visegrad Countries when dealing with Sub-Saharan Africa - Pásztor, Szabolcs (Journal of Central and Eastern European African Studies, 2024)
The paper briefly shows the renewed interest in and fundamental reasons for establishing new diplomatic missions in Sub-Saharan Africa (SSA). Old and new trading partners alike are trying to create more embassies and consulates because they strive to help the private sector by preparing the ground for bilateral trade. The Central and Eastern European (CEE), and the Visegrad (Czech Republic, Hungary, Poland, and Slovak Republic) countries have been following the international tendencies and they have place and increased emphasis on their diplomatic missions in the hope of diversifying their exports. After synthesizing the related literature, the second part of the paper argues that embassies and consulates directly contribute to stronger bilateral trade links. It seems that by opening more embassies in the SSA region the V4 countries could find alternative markets for their products and services so the embassies count to be growth opportunities. By fostering stronger economic and political ties both regions could benefit from the new scramble for diplomatic missions in various forms.